Biodegradable Silk Fibroin Nanocarriers to Modulate Hypoxia Tumor Microenvironment Favoring Enhanced Chemotherapy - Bin, Li; Yang, Yuxiao; Wang, Feiyu; Wang, Rong; Fei, Hongxin; Duan, Siliang; Huang, Linling; Liao, Na; Zhao, Shimei; Ma, Xinbo (Frontiers in Bioengineering and Biotechnology, 2022)
Biopolymer silk fibroin (SF) is a great candidate for drug carriers characterized by its tunable biodegradability, and excellent biocompatibility properties. Recently, we have constructed SF-based nano-enabled drug delivery carriers, in which doxorubicin (Dox) and atovaquone (Ato) were encapsulated with Arg-Gly-Asp-SF-Polylactic Acid (RSA) to form micellar-like nanoparticles (RSA-Dox-Ato NPs). The RGD peptide was decorated on micellar-like nanoparticles, promoting tumor accumulation of the drug. Meanwhile, Ato, as a mitochondrial complex III inhibitor inhibiting mitochondrial respiration, would reverse the hypoxia microenvironment and enhance chemotherapy in the tumor. In vitro, the biopolymer alone showed extremely low cytotoxicity to 4T1 cell lines, while the RSA-Dox-Ato demonstrated a higher inhibition rate than other groups. Most significantly, the ROS levels in cells were obviously improved after being treated with RSA-Dox-Ato, indicating that the hypoxic microenvironment was alleviated. Eventually, SF-based targeted drug carrier provides biocompatibility to reverse hypoxia microenvironment in vivo for enhancing chemotherapy, strikingly suppressing tumor development, and thereby suggesting a promising candidate for drug delivery system.